MMP-9 ACTIVITY DETERMINES THE EARLY RESPONSE TO TREATMENT WITH SPIRONOLACTONE IN RESISTANT HYPERTENSION. (June 2018) - Rodríguez-Sánchez, E.; Navarro-García, J.A.; Aceves-Ripoll, J.; Álvarez-Llamas, G.; Cuesta, F. De La; Segura, J.; Barderas, M.G.; Ruilope, L.M.; Ruiz-Hurtado, G.
Abstract : Objective: Fourth-line treatment with spironolactone significantly ameliorates blood pressure (BP) in resistant hypertension (RH), although not all patients have the desired response. Mechanisms specifically related to RH remain unknown but pathophysiological mechanisms altered in hypertension cause the dysregulation of other processes including vascular remodelling. One of the mechanisms related to vascular remodelling is the activation of the matrix metalloproteinase (MMP)-9. The purpose of this study was to evaluate the MMP-9 profile in RH patients and its predictive value as biomarker of responsiveness to treatment with spironolactone. Design and method: This retrospective study included 36 patients with an office BP above 140/90mmHg and the concomitant use of 3 or more antihypertensive drugs. 24-hours BP was monitored by ambulatory blood pressure measurement (ABPM). Patients above 135/80mmHg were considered as RH and those below, pseudoresistant hypertensives (PRH). Spironolactone was prescribed to patients with RH at 25–50 mg/day, and early response was assessed after 2 months by ABPM. Patients with 24-h BP below 135/85mmHg were reclassified as controlled RH (CRH), and patients above were considered non-controlled RH (non-CRH). MMP-9 activity was assessed by zymography in polyacrylamide gel and by commercial ELISA (QuickZyme Biosciences). Results: MMP-9 activity is significantly increased in patients with RH compared with PRH (P < 0.05) at baseline, and positively correlates with 24-h systolic BP (r = 0.43; P = 0.009) and central systolic BP (r = 0.48; P = 0.003). Reanalysis of baseline parameters after assessing the early response to treatment with spironolactone indicates that non-CRH patients have a significant increase in MMP-9 activity, 24-h pulse pressure and pulse wave velocity (PWV) compared to CRH patients (P < 0.05). In fact, if patients are classified according to MMP-9 activity, 61% of CRH are below the median and 67% of non-CRH are above the median. Before starting treatment with spironolactone, MMP-9 activity (AUC = 0.75; P = 0.046) and 24-h pulse pressure (AUC = 0.81; P = 0.009) effectively discriminate between CRH and non-CRH patients, with a cut-off value of 14.8ng/ml and 51mmHg respectively. Conclusions: Early response to spironolactone as add-on treatment in RH is determined by the basal level of arterial stiffness estimated by the marker of extracellular matrix remodelling MMP-9 and pulse pressure.